PERFORMANCE ANALYSIS OF THE ROAD SOEKARNO HATTA KM.1-KM.4 SUB-DISTRICT LOA JANAN DISTRICT KUTAI KARTANEGARA - SETIAWAN, DINOE AGENG (KURVA S JURNAL MAHASISWA, 2020)
Soekarno Hatta road km.1-Km.4 loa janan sub-district in Kutai Kartanegara Regency is a secondary arterial road connecting one primary and secondary area to another. Land use conditions contained in the Soekarno Hatta road segment km.1-Km.4 loa janan sub-district are dominated by public buildings with public activities, namely Settlements, Commercials and Offices. Jalan Soekarno Hatta km.1-Km.4, loa janan sub-district belongs to the category of class III roads. As the economy develops and the level of population prosperity will result in increased levels of traffic travel, which occurs due to the need for transportation from the community, where people will always look for faster, safer and smoother roads. The increase in population and the number of urbanization to urban areas will cause a level of movement and density, so that the need for transportation also increases. Based on this, a study was conducted on the performance of Jalan Soekarno Hatta km.1-Km.4 in the sub-district loa janan in Kutai Kartanegara Regency. As for the Performance Analysis of the Soekarno Hatta Road Section km.1-Km.4, the sub-district of the district uses the Indonesian Road Capacity Manual (MKJI'997), which is described based on the UR-1 Form in the form of General Conditions and Geometric of roads, UR-2 in the form of data advanced input, namely Traffic Flow and Composition and side barriers, UR-3 in the form of Analysis of the free flow speed of light vehicles, the capacity and speed of light vehicles. In the study of Performance Analysis of Soekarno Hatta Road Section km.1-Km.4, the sub-district of Loan janan conducted a peak hour survey and the survey was conducted at 07.00-22.00. After calculating the available data, Karel Satsut Tubun is 1480.76 pcu / hour and the service level is at level C, which means the current zone is stable, the driver is limited to choosing speed.